Tokens of exchange the problem of translation in global circulations - Liu, Lydia He (Post-contemporary interventions, 1999)
The question of meaning-value in the political economy of the sign / Lydia H. Liu -- Translating the untranslatable : from Copula to incommensurable worlds / Roger Hart -- Demystifying Qi : the politics of cultural translation and interpretation in the early Jesuit mission to China / Qiong Zhang -- Always multiple translation, or, how the Chinese language lost its grammar / Haun Saussy -- Legislating the universal : the circulation of international law in the nineteenth century / Lydia H. Liu -- Japan's engagement with international terms / Alexis Dudden -- Looting Beijing : 1860, 1900 / James Hevia -- The gramophone in China / Andrew F. Jones -- Handmaids to the gospel : Lam Qua's medical portraiture / Larissa N. Heinrich -- Translating homosexuality : the discourse of Tongxing'ai in Republican China (1912-1949) / Tze-Lan Deborah Sang -- Translating psychiatry and mental health in twentieth-century China / Nancy N. Chen -- The Bathos of a universalism : I.A. Richards and his basic English / Q.S. Tong -- Chinese "Revolution" in the syntax of world revolution / Jianhua Chen -- The question of culture in global English language teaching : a postcolonial perspective / Wan Shun Eva Lam